The UGC: Financing of Higher Education in India - Francis, Janailung Kamei (JOURNAL OF INDIAN EDUCATION, 2012)
This paper deals with the emerging issues in public financing of higher education. The funding mechanism of the government-funded institutions and the role of the UGC in this regard, an apex and statutory body by an Act of Parliament solely responsible for the disbursement of grants to all the eligible colleges and universities in the country need to be studied. The UGC in India is not merely a grants giving agency but it is also concerned about the coordination and maintenance of standards. It has to shoulder wide-ranging responsibilities in the process of coordination and maintenance of standards, allocation and disbursement of grants. All these responsibilities are now being challenged as the share of private sector grows and the public sector seems to be keen to partner with the private sector, country opens up to the globalising forces and more importantly the government faces fiscal constraint in a federal set-up. ‘Value for money’, accountability and veering towards competitive funding are the emerging trends world over. Higher education in India needs a huge amount of resources not merely to provide good quality of education but to transform the nation as a whole. The Commission disburses more fund to Central Universities as compare to State Universities. And even within the Central Universities there exist disparities in disbursement of fund. In fact, only some of the reputed Central Universities received a larger share of the funds from the Commission. Higher education in India suffers as the fund is allotted more on maintenance and less on the development expenditure.